Effect Of Palm Shell Waste As A Filler In AC-WC Using Local Aggregate - Louise Elizabeth; Celvin Stevianus Mangago Jati; Elizabeth (MULTITEK INDONESIA, 2026)
The rise in palm oil production in Indonesia generates large amounts of palm shell waste, which can pollute the environment if not properly managed. This study analyzes the characteristics of So'do River aggregate and the effect of using palm shell waste as a filler on Asphalt Concrete – Wearing Course (AC-WC) mixtures. Laboratory experiments used 60/70 penetration asphalt with 6.50% asphalt content. Cement filler was partially replaced with palm shells at 0%, 25%, 50%, 75%, and 100%. Marshall tests were conducted following the 2018 General Bina Marga Specifications Revision 2 to measure stability, flow, VIM, VMA, and VFB. Results indicate that So'do River aggregate meets technical standards, and palm shell filler affects AC-WC mixture properties, particularly stability and volumetric parameters. The best stability occurred at a 50% palm shell–50% cement ratio. Some substitution levels still comply with specifications, showing palm shell waste has potential as a sustainable alternative filler in AC-WC mixtures.